Penerapan Range Of Motion Aktif Terhadap Pemulihan Kekuatan Otot Dan Sendi Pada Pasien Post Op Fraktur Ekstremitas Di Ruang Bedah RSUD Pandan Arang Boyolali - Iiq Widowati Suryaning Putri; Hermawati Hermawati; Panggah Widodo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: The prevalence of fractures in Indonesia is quite high, namely the incidence of fractures in the lower extremities is 46.2%. The habit of patients with extremity fractures does not mobilize, causing a negative impact on muscle and joint strength, namely physical mobilization barriers and followed by muscle atrophy. One of the efforts to improve muscle and joint strength is to do Range Of Motion independently. Objective: To determine the application of active Range Of Motion to muscle and joint strength in post op patients with extremity fractures in the operating room of RSUD Pandan Arang Boyolali. Method: This application is descriptive in the form of a case study conducted on 2 respondents using the standard operating procedure Range of Motion and the MMT (Manual Muscle Testing) observation sheet. Findings: Before and after the application of active Range Of Motion, recovery of muscle and joint strength was obtained in the two respondents, Mrs. R from the value of bad muscle and joint strength to good and Mrs. S of the value of muscle and joint strength is slightly worse. Implication There are differences in development before and after active Range Of Motion in fracture post op patients